Experiência cartografada : eventos de arte e afetos - Silva, Ana Lia Rodrigues da (2021)
This work talks about the route at three art events – Documenta of Kassel Germany, 2017; Bienal de São Paulo, Brazil, 2018; and BoCA - Biennial of Contemporary Arts, Portugal, 2019. The Experience in these events is cartographed from the affective perspective and elaborated in analysis as transversalities related to the object, poetics and context. During the survey of the works, intersections are made with the question of temporality as a modifier of experience, a premise that meets the chosen methodology, affective cartography. Hybrid qualities of the object are observed as a result of contamination of contemporary media, however, the analyses cover beyond the objects the possible ways of making art of that time.